Open Innovation in Healthcare Ecosystem: A Systematic Review - Torab-Miandoab, Amir; Rezaei-Hachesu, Peyman; Samad-Soltani, Taha (Journal of Health Management, 2024)
Several countries are facing significant troubles of health services, particularly rising prices. Innovative technologies and services are expected to help boost medical quality and cut costs. In this sense, there is a lack of innovative work in spite of a growing interest in open innovation and approaches that advocate for expanded cooperation among various actors in healthcare. This article describes the findings of a study concerning the commitment of the healthcare sector to open innovation. The search for literature focused on English-language papers up to 12 January 2020. Based on the indicated criteria for inclusion, 29 articles were included. The results show that most experiments concentrate on the areas of pharmaceutical research (drug discovery) and health informatics (health information systems and infrastructures) that were brought out as concepts or applied as pilots and prototypes. The participation of the healthcare sector is limited in open innovation, and more work is required with an emphasis on how to get open innovation.
Keywords: Health Informatics; Health Services; Open Innovation; Healthcare Ecosystem